2014
DOI: 10.1002/asia.201301562
|View full text |Cite
|
Sign up to set email alerts
|

Chemico‐Physical Synthesis of Surfactant‐ and Ligand‐Free Gold Nanoparticles and Their Anti‐Galvanic Reduction Property

Abstract: Galvanic reduction (GR) is a classic reaction. In simple terms, metals can reduce less reactive (or more noble) metal ions, while the opposite--metals reduce more reactive (or less noble) metal ions--should not occur. However, recently we found that anti-galvanic reduction (AGR) occurred to thiolated gold and silver nanoparticles. However, the essential issue whether the occurrence of AGR requires the assistance of reductive thiolate ligands or not still remained unanswered. In this work, by using a novel prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…To confirm that the reaction between Ag 25 (SR) 18 and Pd 2+ is a galvanic reaction, XPS analyses are conducted. The binding energies of Pd 3d5/2 (337.3 eV) and Pd 3d3/2 (342.5 eV) in Ag 4 Pd 2 (SR) 8 are slightly shifted to the negative compared with those of Pd 3d5/2 (337.4 eV) and Pd 3d3/2 (342.7 eV) in the Pd‐thiophenol complexes, while the binding energies of Ag 3d5/2 (368.9 eV) and Ag 3d3/2 (375 eV) are positively shifted in comparison with those of Ag 3d5/2 (368.1 eV) and Ag 3d3/2 (374.2 eV) in Ag 25 (SR) 18 and close to those of cation silver, see Figure . In other words, Pd 2+ is reduced to some extent in the formation of Ag 4 Pd 2 (SR) 8 , albeit it cannot be reduced to neutral charge forming PdAg 24 (SR) 18 similar to the case in the formation of AuAg 24 (SR) 18 by way of a GR reaction between Ag 25 (SR) 18 and Au 3+ .…”
mentioning
confidence: 98%
“…To confirm that the reaction between Ag 25 (SR) 18 and Pd 2+ is a galvanic reaction, XPS analyses are conducted. The binding energies of Pd 3d5/2 (337.3 eV) and Pd 3d3/2 (342.5 eV) in Ag 4 Pd 2 (SR) 8 are slightly shifted to the negative compared with those of Pd 3d5/2 (337.4 eV) and Pd 3d3/2 (342.7 eV) in the Pd‐thiophenol complexes, while the binding energies of Ag 3d5/2 (368.9 eV) and Ag 3d3/2 (375 eV) are positively shifted in comparison with those of Ag 3d5/2 (368.1 eV) and Ag 3d3/2 (374.2 eV) in Ag 25 (SR) 18 and close to those of cation silver, see Figure . In other words, Pd 2+ is reduced to some extent in the formation of Ag 4 Pd 2 (SR) 8 , albeit it cannot be reduced to neutral charge forming PdAg 24 (SR) 18 similar to the case in the formation of AuAg 24 (SR) 18 by way of a GR reaction between Ag 25 (SR) 18 and Au 3+ .…”
mentioning
confidence: 98%
“…[14] In this background some recent reports claim that small NPs of more noble metals such as Au and Pt can reduce less noble metal ions like Ag + which is a deviation from the conventional free energy based arguments used for Galvanic displacement. [15][16][17] This phenomenon has been termed as Anti Galvanic Reduction (AGR). In some of these methods ligand protected Au NPs were used to which a silver precursor is added subsequently.…”
Section: Introductionmentioning
confidence: 98%
“…These observations confirmed that the AGR occurred. [31] These authors found that surfactant-free and ligand-free noble-metal NPs such as Au, Pt, and Pd have a distinct reducing ability with regard to less noble ions such as those of Ag and Cu when the size of noble MNPs reduces to less than 3 nm. XPS and mass spectroscopy confirmed that Cu 2+ and Ag + were reduced, respectively to Cu 0 and Ag 0 , by AgNPs and Au NPs.…”
Section: Introduction To the Anti-galvanic Reactionsmentioning
confidence: 99%
“…[29] Two years later, the general concept of AGR was first proposed by Wu. [31] Since then began the new era of anti-galvanic reactions (AGRs) that will be discussed in the second part of this review. [30] Later this author repudiated his previous conjecture and confirmed that the AGR system does not require the cooperation of reductive ligands, and that it is a natural property of the ultrathin nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation